A Technological Approach to Support Extensive Livestock Management in the Portuguese Montado Ecosystem - João Serrano; Luís Roma; Shakib Shahidian; Anabela D. F. Belo; Emanuel Carreira; Luís L. Paniagua; Francisco Moral; Luís Paixão; José Marques da Silva (Agronomy, 2022)
Extensive livestock production systems based on improved pastures under Montado of Holm oaks represent an approach in line with the challenges of sustainability and biodiversity. The increasing incorporation of technologies in the monitoring of this ecosystem allows for a better knowledge of the spatial and temporal variability and, consequently, a more economically profitable management. In this study, between July 2020 and June 2021, soil and pastures were monitored in a 20 ha Montado area located in Alentejo (Southern Portugal) and used for extensive grazing of cattle. The survey of soil apparent electrical conductivity (ECa), the application of algorithms for definition of homogeneous management zones (HMZ), the use of indices obtained from satellite imagery time series to characterize the evolution of pasture quality and the soil and pasture sampling, including the identification of bio-indicator botanical species, were the basis of this exploratory study, allowing a holistic approach to this complex soil-pasture-trees and animals ecosystem. In the near future, this knowledge could represent an important milestone in providing decision-making support systems to farm managers in terms of smart sampling, differential application of fertilizers, amendments or seeds, choosing the best spacing and density of trees in this ecosystem, promoting dynamic grazing, or identifying the animal feed supplementation needs in the critical periods of the year.